Reflections of Digitalization on Painting - Aydogan, D. (EDITOGRAFICA S R L, 2019)
New media has provided diversity in art in terms of medium and tools. Art has entered a new period with collective production processes and forms. Different techniques, applications, production and sharing forms have emerged with digitization in painting. With the multi-faceted structure of art in digital environment, painting has become more disciplinary compared to previous periods, and has become closer to different fields and branches of art. In addition to traditional painting practices, the ability to create digital images has brought a different perspective to the art of painting. On the other hand, digital artists that emerged in response to traditional artists have expanded their production methods to a wider range. In addition to the innovations in production, as new issues in the presentation methods have an impact on the arts, new discussion issues have risen. Furthermore, it can be thought that the definition of art creates confusion due to the diversity and intensity of production in the digital environment. Reproduction, duplication and modification of a work of art for different purposes bring the issues of quality, quantity and aesthetics into question. In this study, the state of the art of painting will be examined based on the production and presentation forms in digital media.
Keywords: Painting in New Media; Digital Painting; Digital Art; Technology and Art; Digitalization; Cultural Studies; Communication